Can Other Comprehensive Income be Used for Tax Avoidance? - Marhaendra Kusuma; Puji Rahayu (Jurnal Akuntansi dan Keuangan, 2022)
Other Comprehensive Income (OCI) is the impact of applying fair value accounting, namely the difference between the fair value of assets (liabilities) and their carrying values. Uncertainty about the time and amount of OCI which is a medium for tax avoidance. This study provides empirical evidence whether OCI can be used for tax avoidance, data from 504 companies listed on the IDX for 2016 – 2020. The results show that companies in Indonesia do not carry out earnings management for tax avoidance through OCI, companies in Indonesia consistent in realizing OCI according to the plan for the previous period, there is no time delay or change in the amount of OCI realization. The novelty of this study lies in the effect of OCI on tax avoidance, in addition to previous literature such as the influence of governance, political connections, foreign interests, legal systems, and CSR.